Use of a molecular signal response classifier informs treatment selection and improves outcomes in Hispanic patients with rheumatoid arthritis - Karpouzas, George A.; Rodriguez, Miguel; Bui, Viet L.; Strand, Vibeke; Ormseth, Sarah R. (Frontiers in Musculoskeletal Disorders, 2026)
ObjectiveIn this study, we evaluated the performance of a molecular signal response classifier (MSRC) predicting a signal of inadequate response (SIR) to tumor necrosis factor-α inhibitors (TNFis) in Hispanic patients with rheumatoid arthritis. We explored whether the MSRC informed treatment selection and improved outcomes over standard of care.MethodsWe compared 108 MSRC-tested patients with 206 untested controls. Outcomes included the low clinical disease activity index (CDAI-LDA, <10), minimum clinically important difference (CDAI-MCID), low Routine Assessment of Patient Index Data-3 (RAPID3-LDA), low patient global assessment of disease (PtGA-LDA), and minimal pain visual analog scale score (all ≤2 on a 0–10 scale).ResultsSeventy (64.8%) MSRC-tested patients exhibited an SIR; those received TNFis less frequently than controls [14.3% vs. 57.8%, adjusted odds ratio (aOR) 0.12 (95% confidence interval, CI, 0.06–0.25)]. Patients with an MSRC-aligned treatment selection more frequently reported CDAI-LDA [aOR 9.79 (1.70–56.58)], CDAI-MCID [aOR 6.49 (1.18–35.71)], RAPID3-LDA [aOR 11.55 (1.42–93.81)], PtGA-LDA [aOR 9.74 (1.11–85.64)], and minimal pain [aOR 6.98 (1.14–42.59)] compared with misaligned ones. Compared with controls, MSRC-aligned patients more commonly reported PtGA-LDA [aOR 1.76 (1.00–3.11)] and minimal pain [aOR 1.94 (1.08–3.51)]. Among biologic disease-modifying antirheumatic drug (bDMARD)-naïve participants, MSRC-aligned patients more frequently reported CDAI-LDA [aOR 3.67 (1.31–10.26)], CDAI-MCID [aOR 5.17 (1.05–25.47)], PtGA-LDA [aOR 3.20 (1.25–8.19)], and minimal pain [aOR 2.90 (1.07–7.85)] vs. controls. In TNFi-treated patients, the MSRC predicted SIR by CDAI-LDA with positive predictive value = 80.0% (95% CI 55.5–97.5%), sensitivity = 50% (95% CI 29.9–75.4%), specificity = 86.7% (95% CI 68.1–98.3%), and area under the curve = 0.68 (0.53–0.84).ConclusionsMost Hispanic patients exhibited an SIR to TNFis. MSRC-aligned therapy improved outcomes vs. the MSRC-misaligned group and untested controls, predominantly among bDMARD-naïve patients.